Strategi Pengelolaan Sumber Daya Alam Sebagai Pondasi Transformasi Ekonomi yang Inklusif dan Berkelanjutan di Provinsi Kepulauan Riau - M. Ferdi Septianda (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
Inclusive and sustainable economic transformation in Riau Islands Province (Riau Islands) is significant, it can be done by making natural resources (SDA) as a foundation. However, it faces challenges such as environmental damage, social conflict, and dependence on non-renewable resources. This research aims to find strategies for managing natural resources as a foundation for inclusive and sustainable economic transformation in Riau Islands Province, in terms of several relevant concepts that can be integrated, such as Sustainable Development Goals (SDGs), Green Economy (GE), Blue Economy (BE), and Economic Democracy (EK). The research method used is a qualitative literature study by collecting information from books, scientific articles, and government documents. First, through the concept of SDGs, sustainable development can be implemented by empowering local communities, ensuring equitable and inclusive resource management, minimizing environmental damage, and promoting access to a natural resource-based economy. Second, through the GE concept, sustainable development can be carried out by mapping resource potential, developing environmentally friendly sectors, increasing human resource capacity, developing multi-stakeholder partnerships, building supporting infrastructure, and implementing strict monitoring and evaluation mechanisms. Third, through the BE concept, research focuses on mapping and evaluating marine resources, encouraging investment and infrastructure, involving coastal communities, increasing community capacity through training, prioritizing the protection of marine ecosystems, and mitigating environmental impacts. Fourth, through the representation of the EK concept, the Government can involve the community in policy-making, empowering the local economy, equalizing access to natural resources, and enforcing environmental regulations in maintaining the sustainability of natural resource management.